Sacral Curvature in Addition to Sacral Ratio to Assess Sacral Development and the Association With the Type of Anorectal Malformations - Chen, Zhen; Zheng, Lingling; Zhang, Minzhong; Zhang, Jie; Kong, Ruixue; Chen, Yunpei; Liang, Zijian; Levitt, Marc A.; Wei, Chin-Hung; Wang, Yong (Frontiers in Pediatrics, 2021)
Introduction Sacral ratio (SR) is currently the only measurement to quantitatively evaluate sacral development in patients with anorectal malformations (ARM). This study proposes sacral curvature (SC) as a new indicator to qualitatively assess the sacrum, and hypothesizes that sacral development, both quantitatively and qualitatively, can be an indicator of the type of ARM. The study aims to investigate the difference between SR and SC in ARM patients and the potential for these to predict the type of ARM. Methods and Materials This study was retrospectively conducted between August 2008 and April 2019. Male patients with ARMs were enrolled and divided into three groups based on the types of ARM: (1) rectoperineal fistulae, (2) rectourethral-bulbar fistulae, and (3) rectourethral-prostatic or rectobladder-neck fistulae. SC was measured in the sagittal views of an MRI or a lateral radiograph of the sacrum. Results 316 male patients with ARMs were included. SRs were 0.73 ± 0.12, 0.65 ± 0.12, and 0.57 ± 0.12 in perineal, bulbar, and prostatic/bladderneck fistula, respectively (p < 0.01). The SCs in perineal fistulae and bulbar fistulae were significantly higher than that in prostatic/bladderneck fistulae (0.25 ± 0.04, 0.22 ± 0.14, and 0.14 ± 0.18, p < 0.01). When SR ≥ 0.779, there was an 89.9% of possibility that the child has a perineal fistula. When SR ≤ 0.490 and SC ≤ 0, the possibilities of the child having prostatic/bladderneck fistulae were 91.6% and 89.5%, respectively. SC < 0 was also noted in 27 (27.8%), 19 (10.5%), and no (0%) patients of prostatic/bladderneck, bulbar, and perineal fistulae (p < 0.01), respectively. Sacral defect was noted in 63% of patients with SC ≤ 0, compared to none with SC > 0 (p < 0.01). Conclusions The higher the rectal level is in an ARM, the lower are the objective measurements of the sacrum. SC ≤ 0 is associated with sacral defect and implies a high likelihood of prostatic/bladderneck fistulae. Keywords: anorectal malformations; sacral ratio; sacral curvature; sacral development; sacral defect.